(untitled) (Research, Society and Development, 2019)
This study aimed to verify the vision of preceptors about the preceptory and the reception of undergraduate students in Primary Health Care (PHC). A descriptive-exploratory qualitative study was carried out with preceptors from the PHC health services of the North District / Baltazar Hub of Porto Alegre / RS. It was approved by the Ethics Committee of the Federal University of Health Sciences of Porto Alegre and the Municipal Health Department of Porto Alegre. The sample consisted of 31 preceptors. The preceptors were from nursing, pharmacy, speech therapy and nutrition courses. The information was collected individually through a semi-structured questionnaire, with closed and open questions. The data of the study were evaluated according to the content analysis of the thematic type. The study showed that 93% of respondents are satisfied to perform the preceptory. They reported difficulties and facilities regarding the reception of students. Difficulties can negatively impact the academic performance of trainees in PHC. It is important that the preceptor has subsidies for a qualified teaching, such as training, permanent meetings with teachers, among others. In this way the student will have a good use of the stage that to realize.